Time for the Ancients : Measurement, Theory, Experience. - Singer, P. N. (Berlin/Boston : Walter de Gruyter GmbH, 2022)
Chronoi: Time, Time Awareness, Time Management　is a book series that presents the work of the Einstein Center Chronoi. The center is dedicated to the investigation of time and time-related subjects such as time awareness, time management, time perception, and temporality from interdisciplinary and transdisciplinary perspectives.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books